Use of the framework species method to restore carbon flow via litterfall and decomposition in an evergreen tropical forest ecosystem, Northern Thailand - Nuttira Kavinchan (2018)
© 2015, Kasetsart University. All right reserved. If forest restoration is to play a significant role in mitigating climate change, greater knowledge is needed of how quickly the process can restore carbon flows to levels typical of natural forest. Litterfall and its decomposition are two important components of the carbon cycle of tropical forest ecosystems. This paper quantified the balance between these two processes in experimental plots undergoing restoration of upland evergreen forest by the framework species method in the upper watershed of the Mae Sa Valley, Chiang Mai province, northern Thailand. Restoration plots had been planted with 20–30 indigenous forest tree species at an average initial density of 3,100 trees.ha -1 in 1998, 2002 and 2007 (at 11, 7 and 2 yr, respectively, before the study commenced). Carbon flow measurements in these plots were compared with identical measurements in relatively intact mature forest and nonplanted control sites. Measurements were litterfall dry mass (from litterfall traps emptied monthly), percentage carbon content (using the Walkley-Black method) and decomposition rates (using litterbags). Net inputs of carbon into the soil pool via litterfall declined below control levels for at least 7 yr after tree planting (probably due to fire and weeding), but increased rapidly thereafter, reaching 61% of natural forest levels by 11 yr and are projected to reach natural forest levels (1.33 t.ha -1 .yr -1 carbon) in 14–16 yr after tree planting. Therefore, the framework species method appears to be an efficient mechanism for restoring carbon flow through forest ecosystems and should be considered for forest restoration projects where carbon sequestration is included among the objectives.